2014
DOI: 10.1038/eye.2014.258
|View full text |Cite|
|
Sign up to set email alerts
|

Two-year outcome of an observe-and-plan regimen for neovascular age-related macular degeneration: how to alleviate the clinical burden with maintained functional results

Abstract: Two-year outcome of an observeand-plan regimen for neovascular age-related macular degeneration: how to alleviate the clinical burden with maintained functional results This article has been corrected since advance online publication and a corrigendum is also printed in this issue C Gianniou, A Dirani, W Ferrini, L Marchionno, D Decugis, A Deli, A Ambresin and I Mantel AbstractPurpose The purpose of this study was to report the 2-year outcome of an individually tailored 'observe-and-plan' treatment regimen for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
34
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 29 publications
1
34
0
Order By: Relevance
“…Thus, the excellent and stable functional results over 2 years using the Observe-and-Plan regimen served as clinical validation of the regimen. 20 Although functional validation of the regimen is essential, the main interest of the Observe-and-Plan regimen was to achieve these results with fewer visits and an individualized number of injections, which are the main factors impacting the clinical burden: We found that a mean of four visits after baseline was needed during the first year, and this was reduced further to 2.9 visits during the second year. The mean numbers of injections were 7.8 in the first year (including loading doses) and 5.8 in the second year, which were quite similar to other variable-dosing regimens (Fig.…”
Section: Perspectivementioning
confidence: 89%
See 3 more Smart Citations
“…Thus, the excellent and stable functional results over 2 years using the Observe-and-Plan regimen served as clinical validation of the regimen. 20 Although functional validation of the regimen is essential, the main interest of the Observe-and-Plan regimen was to achieve these results with fewer visits and an individualized number of injections, which are the main factors impacting the clinical burden: We found that a mean of four visits after baseline was needed during the first year, and this was reduced further to 2.9 visits during the second year. The mean numbers of injections were 7.8 in the first year (including loading doses) and 5.8 in the second year, which were quite similar to other variable-dosing regimens (Fig.…”
Section: Perspectivementioning
confidence: 89%
“…2). 9,12,15,20 However, the number of visits was three to four times less than what would be needed in PRN with monthly visits 9 and less than half of what is needed in the Treat-and-Extend regimen (Fig. 2).…”
Section: Perspectivementioning
confidence: 99%
See 2 more Smart Citations
“…If there was no recurrence at 3 months, the patient could change to monitoring alone. This approach is based on the highly predictable behaviour of recurrent activity in a certain patient with neovascular AMD [37][38][39].…”
Section: Observe and Planmentioning
confidence: 99%